Orgullo mestizo. El baloncesto como valorización de la diferencia entre hijos de inmigrantes en Sevilla - Castellani, S. (Studi Emigrazione, 2016)
Dominant political discourse on migrants' children in Spain, as well as in other countries, points at sport as a main resource for "integration" in the host society. The use of sport should promote the "suspension" of differences between the majority of the population and the existing ethnic minorities. The literature on migrants' sports practices shows that migrant minorities use sport as a tool for gaining visibility in the public space as well as for facing stigmatization. Up to now, however, few researches have focused on migrants' children. Besides, most of these studies looked at inter-ethnic relations, paying little attention to intergenerational relations between minors and adults as for the potential difference in terms of their transnational migratory projects. Drawing from a study carried out along three years with youth basketball teams boosted by a Latin American association in the city of Seville in Spain, this paper looks at migrants' sport practices through the lens of a "ritual analysis" and it shows how, thanks to basketball, teenagers gain visibility in the public spaces and they are able to re-define on the playground their interethnic, inter-generational and gender relations. Finally, this study illustrates how these young people transform the stigma into an emblem, reaffirming their own generational differences in relation to both adults and the host society.